Sorção de resíduos da indústria sucroenergética na obtenção de agronutrientes - Antonio, Milena Maria (2023)
Productive processes aim for efficiency, profitability, and environmental sustainability, necessitating waste management to prevent environmental impacts. In the agro-industrial sector, vinasse and the ashes from sugarcane bagasse burning (SCBA) are prominent by-products in the sugar and energy industry. The first is a substance with nutritional value for fields but exhibits specific properties that could harm the environment in the long term. The second is a solid material with valuable adsorptive characteristics for effluent treatments. This project aimed to apply the adsorption capacity of SCBA to adsorb nutrients N, P, and K from vinasse and improve the characteristics of these agro-industrial wastes for subsequent use in agriculture. The washed/dried CBCA was initially used in sorption experiments with NH4+, K+, and total P from simulated standard solutions of K2SO4 and (NH4)2HPO4, representing the vinasse concentrations. Analyzing the ashes before and after sorption experiments was essential to explain their performance. Different characterization techniques (FTIR, XRD, BET, SEM, TGA, and DSC) showed that CBCA is a micro-mesoporous, heterogeneous material with irregular, fibrous tubular, spherical, and prismatic particles containing SiO2 in the form of quartz and cristobalite. Besides, smaller masses of ashes with a contact time of 6 h were promising with standard simulated solutions for N, P, and K sorption evaluation. The same ideal systems were replicated for vinasse, requiring adjustment of the sorption time to 24 h. The results for both tests showed success in kinetics, especially for K+ and NH4+, and allowed the correction of vinasse pH due to the alkaline character of the ashes. However, the sorption behavior of nutrient P was distinct due to factors such as ion size and charge differences and interactions between P and silicon (from CBCA). The sorption kinetic models for K+ and NH4+ present diffusional interaction with the medium, not necessarily controlled only by adsorption on active sites exhibiting non-uniform characteristics. The non-linear Freundlich model also showed adsorption sites with different energy levels and a multilayer sorption process. Therefore, the sorption of nutrients in vinasse is feasible, adding value to waste materials and reducing environmental impact when used in agriculture.